Warthin’s Tumour: A Case Report and Review on Pathogenesis and its Histological Subtypes - Raghu A R; Shweta Rehani; Kundendu Arya Bishen; Shitalkumar Sagari (Journal of Clinical and Diagnostic Research, 2014)
Warthin’s tumour/ Papillary cystadenoma lymphomatosum (PCL) constitutes a minority of salivary gland neoplasms and it is a monomorphic adenoma which primarily involves the parotid gland. Warthin’s tumour shows multiple cysts that have numerous papillations covered by bilayered columnar and basaloid oncocytic epithelium. The connective tissue portion shows proliferation of follicle- containing lymphoid tissue which necessitates careful distinction for diagnosis. Although, Warthin’s tumour presents as a clinically benign, slow-growing, usually asymptomatic lesion with low rates of recurrences and malignant transformation, but still this tumour is considered unique because of its histological appearance and unknown origin and pathogenesis. Here, we report a case of Warthin’s tumour of five years duration in a 50- year-old male patient in the right parotid gland and also review and discuss various concepts concerning the development of this tumour along with a comprehensive literature on its clinic-pathologic features.